Immune Status in Children Before Liver Transplantation—A Cross-Sectional Analysis Within the ChilsSFree Multicentre Cohort Study - Möhring, Tamara; Karch, André; Falk, Christine S.; Laue, Tobias; D'Antiga, Lorenzo; Debray, Dominique; Hierro, Loreto; Kelly, Deirdre; McLin, Valerie; McKiernan, Patrick; Pawlowska, Joanna; Czubkowski, Piotr; et al. (Frontiers in Immunology, 2019)
Background: Both markers of cellular immunity and serum cytokines have been proposed as potential biomarkers for graft rejection after liver transplantation. However, no good prognostic model is available for the prediction of acute cellular rejection. The impact of underlying disease and demographic factors on immune status before pediatric liver transplantation (pLTx) is still poorly understood. We investigated expression of immune markers before pLTx, in order to better understand the pre-transplant immune status. Improved knowledge of the impact of pre-transplant variables may enhance our understanding of immunological changes post pLTx in the future. Methods: This is a cross-sectional analysis of data from the ChilSFree study, a European multicentre cohort study investigating the longitudinal patterns of immune response before and after paediatric LTx. Immune cell counts and soluble immune markers were measured in 155 children 1-30 days before pLTx by TruCount analysis and BioPlex assays. Results were logarithmised due to skewed distributions and then compared according to age, sex and diagnosis using t-tests, ANOVAs, and Tukey post-hoc tests. The association between immune markers at time of LTx and patients’ age was assessed using a fractional polynomial approach. Multivariable regression models were used to assess the relative contribution of each factor. Results: Sex had no effect on immune status. We found strong evidence for age-specific differences in the immune status. The majority of immune markers decreased in a log-linear way with increasing age. T and B cells showed a sharp increase within the first months of life followed by a log-linear decline in older age groups. Several immune markers were strongly associated with underlying diagnoses. The effects of age and underlying disease remained virtually unchanged when adjusting for each other in multivariable models. Discussion: We show for the first time that age and diagnosis are major independent determinants of cellular and soluble immune marker levels in children with end-stage liver disease. These results need to be considered for future research on predictive immune monitoring after pLTx.